2000
DOI: 10.1053/jhep.2000.9603
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of inoperable hepatocellular carcinoma: Estrogen receptors’ status in the tumor is the strongest prognostic factor for survival

Abstract: Clinical course in hepatocellular carcinoma may be very different. We prospectively evaluated 96 patients with hepatocellular carcinoma unsuitable for radical therapy to investigate factors that could influence survival. Clinical, pathologic, and molecular data of patients were analyzed by univariate and multivariate analysis. The overall actuarial probability of survival at year 1, 2, 3, 4, 5, and 6 was 72%, 41%, 38%, 24%, 20%, and 9%. At univariate analysis, alphafetoprotein (AFP) (P ‫؍‬ .0082); alkaline pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
137
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(144 citation statements)
references
References 21 publications
5
137
1
1
Order By: Relevance
“…PVTT can also decrease portal flow that may lead to ascites, jaundice, hepatic encephalopathy, or liver failure. Therefore, the presence of PVTT is one of the most significant prognostic factors of poor prognosis [21,22] , and it has been reported that these patients survive only 2.7-4 mo if left untreated [22,23] . In advanced HCC patients with PVTT, standard treatments have not been established, especially in the Asia-Pacific region.…”
Section: Discussionmentioning
confidence: 99%
“…PVTT can also decrease portal flow that may lead to ascites, jaundice, hepatic encephalopathy, or liver failure. Therefore, the presence of PVTT is one of the most significant prognostic factors of poor prognosis [21,22] , and it has been reported that these patients survive only 2.7-4 mo if left untreated [22,23] . In advanced HCC patients with PVTT, standard treatments have not been established, especially in the Asia-Pacific region.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to a series of other published studies (Chevret et al, 1999;Llovet et al, 1999; The Cancer of the Liver Italian Program, 2000; Villa et al, 2000;Rabe et al, 2001;Herold et al, 2002), this study included a high number of patients treated by TACE and PEI, which have become the most frequently used treatments in the Western World. No patient was excluded from our retrospective analysis in contrast to those studies, who investigated only the effect of surgery or local ablative therapy (Tanaka et al, 1998;Schlitt et al, 1999;O'Suilleabhain et al, 2003;Jaeck et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…18 HBsAg-positive patients with variant estrogen receptor ␣ (ER-␣) were characterized by the worst survival. 19 In this study, we checked the expression of androgen receptor, ER-␣, and ER-␤ in HBV gene knock-in transgenic mice by Northern blot analysis. The expression of androgen receptor and ER-␣ had not been detected in livers of the HBV transgenic mice and controls (data not shown), but the expression of ER-␤ was extremely elevated at the transcriptional level only in the liver tumors developed in male p21-HBsAg transgenic mice (Fig.…”
Section: Up-regulated Expression Of Er-␤ In Tumors Frommentioning
confidence: 99%